Improved Operating Performance of Mining Machine Picks; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Prokopenko S. A. Sergey Arturovich; Li A.; Kurzina I. A. Irina Aleksandrovna; Sushko A. V. Anastasiya Viktorovna (2016, 2016)
Title screen